ChemInform Abstract: An Improved Microwave Assisted Protocol for Yonemitsu‐Type Trimolecular Condensation. Issue 6 (23rd January 2015) - Viola, Angelo; Ferrazzano, Lucia; Martelli, Giulia; Ancona, Sebastiano; Gentilucci, Luca; Tolomelli, Alessandra
Abstract The synthesis of products (IV), (VI) and (VIII), which are obtained as a 60:40 mixture of diastereomers, is accompanied by the formation of significant amounts of bis‐indolated product and non‐reacted starting material.